Dark tourism : theory, interpretation and attraction - Sharma, Anukrati; Arira, Shurti; Shukla, Parag (Building the future of tourism, 2024)
Dark Tourism has seen a surge in popularity in the last decade as people seek a richer travel experience, choosing to meaningfully engage with humankind's more troubling heritage, rather than opting for merely escapist vacations. It is a genre of tourism that has received increased attention in recent years, an umbrella concept for travel to sites that are associated with death and suffering, such as battlefields, prisons, and slave forts. Despite the somewhat morbid nature of many Dark Tourism sites, there is also a positive side. Such sites provide visitors with a chance to reflect on cataclysmic events and draw their own life lessons from events of the past. Dark Tourism: Theory, Interpretation and Attraction is an edited volume drawing on content from around the world. It is relevant for students, scholars, and academicians associated with the fields of memorialization and morality death studies, history, cultural studies, psychology, business management, museology, and heritage tourism studies, as well as religious studies.